2020
DOI: 10.1007/s10278-020-00405-2
|View full text |Cite
|
Sign up to set email alerts
|

The Time Has Come: a Paradigm Shift in Diagnostic Radiology Education via Simulation Training

Abstract: Current radiology training for medical students and residents predominantly consists of reviewing teaching files, attending lectures, reading textbooks and online sources, as well as one-on-one teaching at the workstation. In the case of medical schools, radiology training is quite passive. In addition, the variety of important and high-yield cases that trainees are exposed to may be limited in scope. We utilized an open-source dcm4chee-based Picture Archiving and Communication System (PACS) named "Weasis" in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…e SQL language used by MySQL is the most commonly used standardized language for accessing databases. It has the characteristics of small size and fast speed, which provides protection for simultaneous access by multiple users [35].…”
Section: Construction Of Safety Education Online Learning and Testing...mentioning
confidence: 99%
“…e SQL language used by MySQL is the most commonly used standardized language for accessing databases. It has the characteristics of small size and fast speed, which provides protection for simultaneous access by multiple users [35].…”
Section: Construction Of Safety Education Online Learning and Testing...mentioning
confidence: 99%
“…With the technological development of digital radiographic reconstruction with geometric as well as density characteristic accuracy ( 107 ), more and more VS computer software programs have been designed and used in undergraduate medical education, allowing students gain more hands-on experience and develop their clinical skills without worrying about exposing to any unnecessary radiation. In the recent 2 years, we found five studies ( 20 , 85 , 86 , 88 , 96 ) used VS serious games or systems simulating a radiologist’s practice in the real world among medical undergraduates for radiology learning. The results collectively showed that, for medical undergraduates, the integration of VS as a valuable learning resource had the potential to improve preparation for the clinical environment and increase student confidence ( 20 , 85 , 86 , 88 , 96 ).…”
Section: Resultsmentioning
confidence: 99%
“…In the recent 2 years, we found five studies ( 20 , 85 , 86 , 88 , 96 ) used VS serious games or systems simulating a radiologist’s practice in the real world among medical undergraduates for radiology learning. The results collectively showed that, for medical undergraduates, the integration of VS as a valuable learning resource had the potential to improve preparation for the clinical environment and increase student confidence ( 20 , 85 , 86 , 88 , 96 ).…”
Section: Resultsmentioning
confidence: 99%
“…The virtual simulation experiments of medical technology on iLAB-X were mainly focused on medical radiation and imaging, laboratory diagnosis and dental laboratory technology. In particular, virtual simulation training has been widely used in computerized tomography (CT), magnetic resonance imaging (MRI), and ultrasound practices in undergraduate medical education, and virtual simulation experiments have been demonstrated to be valuable and effective learning resources [ 49–51 ]. Moreover, virtual simulation experiments have also been developed as alternatives to practical nursing education and have effectively promoted nursing neurophysiologyperformance [ 52 , 53 ].…”
Section: Discussionmentioning
confidence: 99%